International validation of the EORTC QLQ-PRT20 module for assessment of quality of life symptoms relating to radiation proctitis: a phase IV study - Halkett, Georgia; Wigley, C.; Aoun, Samar; Portaluri, M.; Tramacere, F.; Livi, L.; Detti, B.; Arcangeli, S.; Lund, J.; Kristensen, A.; McFadden, N.; Grun, A.; et al. (BioMed Central, 2018)
Background: Although patients experience radiation proctitis post radiotherapy no internationally tested instruments exist to measure these symptoms. This Phase IV study tested the scale structure, reliability and validity and cross-cultural applicability of the EORTC proctitis module (QLQ-PRT23) in patients who were receiving pelvic radiotherapy. Methods: Patients (n = 358) from six countries completed the EORTC QLQ-C30, QLQ-PRT23 and EORTC Quality of Life Group debriefing questions. Clinicians completed the EORTC Radiation Therapy Oncology Group scale. Questionnaires were completed at four time-points. The module’s scale structure was examined and validated using standard psychometric analysis techniques. Results: Three items were dropped from the module (QLQ-PRT23 → QLQ-PRT20). Factor analysis identified five factors in the module: bowel control; bloating and gas; emotional function/lifestyle; pain; and leakage. Inter-item correlations were within r = 0.3–0.7. Test-Retest reliability was high. All multi-item scales discriminated between patients showing symptoms and those without symptomology. The module discriminated symptoms from the clinician completed scoring and for age, gender and comorbidities. Conclusion: The EORTC QLQ-PRT20 is designed to be used in addition to the EORTC QLQ-C30 to measure quality of life in patients who receive pelvic radiotherapy. The EORTC QLQ-PRT20 is quick to complete, acceptable to patients, has good content validity and high reliability. Trial registration: Australian and New Zealand Clinical Trials Registry (ANZCTR) ACTRN12609000972224.